Cinema at school: empirical research on the use of films in schools in Valparaíso de Goiás (Revista Contexto & Educação, 2025)
This article has as its central theme the use of films in the classroom and their use as a pedagogical resource in order to enrich the disciplinary content and form students' cultural identity. Conducted field research with a semi-structured questionnaire, where principals and teachers from six municipal public schools in Valparaíso de Goiás were interviewed. The purpose of this work is to present the successes and difficulties of these education professionals, based on their experiences with the cinema in the classroom.
Keywords: Cinema; Education; Classroom; Valparaiso de Goias